2020
DOI: 10.1088/1361-6455/ab7528
|View full text |Cite
|
Sign up to set email alerts
|

Collective excitation of two-dimensional Bose–Einstein condensate in liquid phase with spin–orbit coupling

Abstract: We have studied the collective excitation of Bose–Einstein condensate of short-range weak interacting atoms with spin–orbit coupling (SOC) in two dimensions in the liquid phase. In our study, we have included Rashba, Dresselhaus, as well as Raman SOC. The study of Bogoliubov excitation shows that in small interactions, only phonon modes are present, and for higher interactions, roton modes start to appear. Energy spectra contain two roton modes in relatively strong interacting atomic systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The collective excited state can be considered as ψ exc = ψ + δψ. The perturbation part can be written as [33,34],…”
Section: Collective Excitationmentioning
confidence: 99%
“…The collective excited state can be considered as ψ exc = ψ + δψ. The perturbation part can be written as [33,34],…”
Section: Collective Excitationmentioning
confidence: 99%
“…Depending upon the Rabi and SO coupling parameters range, these soliton-like states are either of single peak (bright soliton) or multiple peaks (stripe soliton) nature [19,21]. Some of these works demonstrate the existence of soliton, as well droplet nature of the self-bound state for the effective one component binary BECs in one dimension [22] and binary mixture with SO coupling in two dimension [20,23]. The transition between the quantum soliton and quantum droplet regime depends on several parameters, like, the atom number (N ), interaction strength, the strength of the confining potential, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since the proposition of the non-trivial attractive nature of the LHY term in quasi-one dimensional quantum droplet [16], it has caught great attention of the scientific community. A significant number of theoretical and numerical works have been performed in recent years using the effective one component [17], binary [18] and SO and Rabi coupled binary BECs [19,20] that explored the structure and dynamics of the Quantum droplet. In SO-coupled BECs, it has been demonstrated that the self-bound states are solitonic for vanishing mean-field contribution [19].…”
Section: Introductionmentioning
confidence: 99%
“…Further Yu et al used this idea in obtaining the ground state phase diagram particularly, excitations of zero momentum phases in quasi-2D SO coupled BECs [46]. In the liquid phase it was demonstrated that the quasi-2D BECs exhibits different excitation modes, like, phonon, roton and double roton modes with different SO couplings as the interaction strengths are varied [47].…”
Section: Introductionmentioning
confidence: 99%